THE FEATURES OF AIRCRAFT FUNCTIONAL SYSTEMS PERFORMANCE MONITORING - S. A. Krotov (Научный вестник МГТУ ГА)
The key steps of aircraft essential parameters and events monitoring during its operation are considered in the article. Conditions for specific risk monitoring are also presented.The notion of fail-safe feature of aircraft functional systems is analysed, and the necessity of continuous process of safety flight level estimate is shown. The method of quantitative assessment of key events and risks probabilities with the use of modern software is proposed. This method contains 5 basic stages: The monitoring parameters setting - this stage is initial and begins with the consideration of organization safety culture, the main purposes and problems determination, the basic parameters and characteristics forming which are to be monitored. The event monitoring in operation - on this stage continuous process of key events searching and monitoring which are a thing of importance within the framework of the established problems takes place. This process is closely related to parameters monitoring set on the first stage. The event and risk estimate - this stage begins directly after the event has been discovered. The estimate process is as long as it is required to identify the event gravity. It also contains the preliminary risk estimate for using in prioritization of initial expanded estimate and in the working out of plan for activities realization. The working out of plan for activities - on this stage correction data is determined that will make changes to aerotechnics working out, operation, maintenance and to staff training directly in linkage to the problem event identified earlier. The activity carrying-out - the realization of actions according to the activity plan. This stage concludes prioritization, planning and problem carrying-out. The dependence set between the probability of failure situations and the degree of their danger is shown. The key factors which are subject to be estimated while aircraft operating and which aim with risk analysis to increase the safety flight level are justified.